PENGARUH PRICE DISCOUNT DAN IN-STORE DISPLAY TERHADAP IMPULSE BUYING (Studi Pada Konsumen di Irian Supermarket Kota Medan) - Sinaga, Hevidora Linny; Damanik, Hanna M.; Purba, Martin Luter (Jurnal KAFEBIS, 2023)
In the current era of globalization, competition between business people in both domestic and foreign markets continues to increase. This is evidenced by the displacement of traditional markets by various types of modern markets, so that many world centers with various shapes and sizes have emerged. The development of this modern retail business is also popping up in every corner of the city, and this has a positive impact on increasing the retail industry in Indonesia. This research was conducted on Irian Supermarket consumers in the city of Medan. The purpose of this study was to determine the effect of price discounts and in-store displays on impulsive purchases at the Irian Supermarket in Medan. This research was conducted on 105 respondents using a purposive sampling method. The method in this study is quantitative with multiple linear regression and using the SPSS 25 program. From the results of the t test, the price discount variable has a not significant positive effect on impulse buying and the in-store display variable has a significant positive effect on impulse buying at Irian supermarkets, Medan city. There is a low (weak) relationship between price discount and in-store display variables as a whole on impulse buying in Irian supermarkets in the city of Medan, namely 15.1% and the rest is influenced by other variables not examined in this study